Features of Political Processes in Central Asian Countries: at the present Stage - E. G. Garbuzarova (Проблемы постсоветского пространства)
In the context of the crisis of the liberal democratic model, authoritarian tendencies strengthen in all Central Asian countries, including Kyrgyzstan. This country demonstrated success in the process of democratic transit for a long time. The purpose of the article is to analyze the content and nature of political processes in Central Asian countries at the present stage. Based on the method of comparative analysis common and distinctive features in the political regimes of the countries of the region are highlighted. The Central Asian countries are grouped according to the principle of recurring trends in domestic political processes. In Central Asian countries, Kyrgyzstan and Tajikistan are the most vulnerable to «color revolutions». The likelihood of such a scenario, fraught with political instability, encourages some political leaders of the countries of the region (Kazakhstan, Uzbekistan) to carry out reforms and design a political regime that more or less proportionally reflects economic reality and social needs, while others (Kyrgyzstan, Tajikistan) resort to methods of «tightening the screws», clearing the space from political opposition. In both cases, this leads to the strengthening of the regime of personal power of the heads of state of the Central Asian countries, and, consequently, the president will continue to remain at the top of the power hierarchy. However, the results of the recent presidential elections in Uzbekistan and the presidential and parliamentary elections in Kazakhstan show that there is a demand for a strong government capable of ensuring socio-political order and stability in these societies.